Clarifying Values: An Updated and Expanded Systematic Review and Meta-Analysis. (October 2021) - Witteman, Holly O.; Ndjaboue, Ruth; Vaisson, Gratianne; Dansokho, Selma Chipenda; Arnold, Bob; Bridges, John F. P.; Comeau, Sandrine; Fagerlin, Angela; Gavaruzzi, Teresa; Marcoux, Melina; Pieterse, Arwen; Pignone, Michael; et al.
Background: Patient decision aids should help people make evidence-informed decisions aligned with their values. There is limited guidance about how to achieve such alignment. Purpose: To describe the range of values clarification methods available to patient decision aid developers, synthesize evidence regarding their relative merits, and foster collection of evidence by offering researchers a proposed set of outcomes to report when evaluating the effects of values clarification methods. Data Sources: MEDLINE, EMBASE, PubMed, Web of Science, the Cochrane Library, and CINAHL. Study Selection: We included articles that described randomized trials of 1 or more explicit values clarification methods. From 30, 648 records screened, we identified 33 articles describing trials of 43 values clarification methods. Data Extraction: Two independent reviewers extracted details about each values clarification method and its evaluation. Data Synthesis: Compared to control conditions or to implicit values clarification methods, explicit values clarification methods decreased the frequency of values-incongruent choices (risk difference, –0.04; 95% confidence interval [CI], –0.06 to –0.02; P < 0.001) and decisional conflict (standardized mean difference, –0.20; 95% CI, –0.29 to –0.11; P < 0.001). Multicriteria decision analysis led to more values-congruent decisions than other values clarification methods (χ 2 = 9.25, P = 0.01). There were no differences between different values clarification methods regarding decisional conflict (χ 2 = 6.08, P = 0.05). Limitations: Some meta-analyses had high heterogeneity. We grouped values clarification methods into broad categories. Conclusions: Current evidence suggests patient decision aids should include an explicit values clarification method. Developers may wish to specifically consider multicriteria decision analysis. Future evaluations of values clarification methods should report their effects on decisional conflict, decisions made, values congruence, and decisional regret.